A randomized phase II trial comparing capecitabine with oxaliplatin or docetaxel as first-line treatment in advanced gastric and gastroesophageal adenocarcinomas. Issue 17 (30th April 2021) - Ni, Lu; Zhang, Weihan; Chen, Ye; Leng, Weibing; Gou, Hongfeng; Hu, Jiankun; Qiu, Meng
Abstract: Background: A combination of fluoropyrimidines and platinum is widely accepted as the standard first-line treatment for advanced gastric and gastroesophageal adenocarcinomas. However, the benefit compared with platinum-free chemotherapeutic regimens remains controversial. We compared the efficacy and safety of capecitabine with oxaliplatin or docetaxel, as first-line therapy in advanced gastric cancer. Methods: Eligible patients were randomly assigned to receive either capecitabine and oxaliplatin (XELOX) (capecitabine 1, 000 mg/m 2 ; twice daily for 14 days with oxaliplatin 130 mg/m 2 on day 1, every 21 days), or DX (capecitabine 1, 000 mg/m 2 ; twice daily for 14 days with docetaxel 75 mg/m 2 on day 1, every 21 days). The primary endpoint was the objective response rate (ORR). Secondary endpoints included the disease control rate (DCR), progression-free survival, overall survival, and prespecified safety endpoints. Results: Ninety patients were enrolled in the West China Hospital from April 2012 to August 2016; a total of 83 and 66 patients were eligible for safety and efficacy analyses, respectively. Between the XELOX and DX groups, ORR (24.2% vs 24.2%, p  = 1.000), DCR (90.9% vs 75.8%, p  = 0.099), progression-free survival (6.1m vs 4.1m, p  = 0.346), and overall survival (8.8m vs 9.0m, p  = 0.973) were similar. There was no significant difference in toxicity between the two regimens. The frequent grade 3 or higher toxicities in the XELOX and DX groups were peripheral neuropathy and hematological toxicity, respectively. Toxicity was tolerable; no treatment-related deaths occurred in either group. Conclusions: The DX regimen was not superior to XELOX, but instead, similar. The platinum-containing regimen remains the preferred first-line option for advanced gastric and gastroesophageal adenocarcinomas, and DX might be considered as an alternative for patients unsuitable for platinum-containing chemotherapy.